8B.002 Getting local ownership of the drowning problem in the Bay of Plenty. (14th March 2021) - McInnes, Neil
Abstract : Context: The Bay of Plenty (BoP) has one of the highest regional drowning rates in New Zealand. In 2017 Water Safety New Zealand (WSNZ) embarked on the development of a regional water safety strategy for BoP. This strategy was focused on reducing drowning deaths and injuries and building a culture of safe enjoyment around water in BoP. Process: The development of the BoP regional water safety strategy was underpinned by direct engagement to build a consensus view on water safety interventions for BoP. A Project Leadership Group of representatives from regional organisations with interest in water safety was established to act as the owners of the BoP strategy development process. Analysis: Regional water safety strategies seek to identify the priority work streams and investment priorities for water safety. To achieve this WSNZ had to ensure greater community ownership of drowning prevention/water safety activities. This meant facilitating regional ownership of both the development and implementation of regional strategy. Outcomes: In June 2019 a BoP water safety strategy document was launched and in September 2019 a strategy manager was recruited to implement the BoP water safety strategy with funding provided by local and national funders. Initiatives that address the priority actions of the strategy were implemented. Learning Outcomes: The most important lesson for WSNZ was the importance of 'hand holding' - maintaining a regional profile even after the strategy was being locally implemented, and being seen to continue to support the recruitment of funders and identification of initiatives.